Effect of modulated microwave frequencies on the physiology of a cyanobacterium, Anabaena doliolum - Rai S.; Singh S.P.; Samarketu; Tiwari S.P.; Mishra A.K.; Pandey K.D.; Rai A.K. (My University, 2025)
The effect of microwave modulated with square waves of different pulse repetition frequencies was studied on the physiologic behavior of the cyanobacterium Anabaena doliolum. The organism was exposed either directly after inoculating the nutrient solution or indirectly by exposing the nutrient solution before inoculation with the cyanobacterium cells for 1 h to microwave (9.575 GHz) modulated with square wave pulse repetition frequencies of 1000, 700, 500, 200, 100, and 50 Hz at a fixed incident power density (0.658 mW/cm2). This study reveals that microwaves athermally induce different biologic effects, perhaps by changing the structures of water. Modulation frequency-dependent water structures appear to cause the biologic effects by differentially partitioning the ions, altering the rate and/or directions of biochemical reactions, or other mechanisms.